2018
DOI: 10.1519/ssc.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Key Phases of the Countermovement Jump Force-Time Curve

Abstract: The countermovement jump (CMJ) test is commonly conducted to assess neuromuscular function and is being increasingly performed using force platforms. Comprehensive insight into athletes' neuromuscular function can be gained through detailed analyses of force-time curves throughout specific phases of the CMJ, beyond jump height alone. Confusingly, however, many different terms and methods have been used to describe the different phases of the CMJ. This article describes how six key phases of the CMJ (weighing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
239
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(295 citation statements)
references
References 28 publications
5
239
0
3
Order By: Relevance
“…This is evident as shown in the significant decrease in time to peak force in Orange in Red in the absence of change in time to take off. One other factor that could have led to change in jump height was the change in jumping strategy [21]. There was a significant increase in time to peak force and a trend for a significant increase in time to take off in UCMJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is evident as shown in the significant decrease in time to peak force in Orange in Red in the absence of change in time to take off. One other factor that could have led to change in jump height was the change in jumping strategy [21]. There was a significant increase in time to peak force and a trend for a significant increase in time to take off in UCMJ.…”
Section: Discussionmentioning
confidence: 99%
“…The CMJ was performed on the same force plate with arms akimbo to prevent any contribution from arm swing. Subjects were instructed to perform each jump as fast and as high as possible by performing the countermovement to their preferred squat depth [21]. Subjects attempted two jumps, separated by 30 s interval.…”
Section: Countermovement Jump Testmentioning
confidence: 99%
“…El CMJ es uno de los test de campo más utilizados para evaluar el estado neuromuscular y cuantificar la fatiga inducida por el entrenamiento en el deportista (Claudino et al, 2017;Gathercole, Sporer, Stellingwerff, & Sleivert, 2015;Marqués-Jiménez et al, 2017;Watkins et al, 2017;Zurutuza, Castellano, Echeazarra, & Casamichana, 2017). Diferentes variables cinéticas y cinemáticas pueden analizarse al evaluar el CMJ (McMahon, Suchomel, Lake, & Comfort, 2018), siendo la altura de salto la más utilizada al poderse obtener de forma práctica y proporcionar información valiosa acerca del estado neuromuscular del deportista (Claudino et al, 2017). Por otro lado, para monitorizar y cuantificar la carga de entrenamiento también se utiliza la percepción subjetiva del esfuerzo (RPE), qué es un método válido, poco costoso, no invasivo y de fácil aplicación que nos permite conocer la carga interna de los deportistas (Campos-Vazquez et al, 2017;Foster et al, 2001;Impellizzeri, Rampinini, Coutts, Sassi, & Marcora, 2004;Marqués-Jiménez et al, 2017).…”
Section: Discussionunclassified
“…Jump height from the force platform was calculated using the impulse -momentum method. The propulsive phase of each CMJ trial was identified using methods described by Chavda et al, (Chavda et al, 2018) and McMahon et al, (McMahon, Suchomel, Lake, & Comfort, 2018). Similar processing was adapted to SJ trials with the exclusion of an unweighting and braking phase.…”
Section: Discussionmentioning
confidence: 99%